What makes space-time interactions in human vision asymmetrical? - Homma, Chizuru T.; Ashida, Hiroshi (Frontiers in Psychology, 2015)
The interaction of space and time affects perception of extents: (1) the longer the exposure duration, the longer the line length is perceived and vice versa; (2) the shorter the line length is, the shorter the exposure duration is perceived. Previous studies have shown that space-time interactions in human vision are asymmetrical; spatial cognition has a larger effect on temporal cognition rather than vice versa (Merritt et al., 2010). What makes the interactions asymmetrical? In this study, participants were asked to judge exposure duration of lines that differed in length or to judge the lengths of the lines with different exposure time; to judge the task-relevant stimulus extents that also varied in the task-irrelevant stimulus extents. Paired spatial and temporal tasks in which the ranges of task-relevant and -irrelevant stimulus values were common, were conducted. In our hypothesis, the imbalance in saliency of spatial and temporal information would cause asymmetrical space-time interaction. To assess the saliency, task difficulty was rated. If saliency of relevant stimuli is high, the difficulty of discrimination task would be low, and vice versa. The saliency of irrelevant stimuli in one task would be reflected in the difficulty of the other task, in the pair of tasks. If saliency of irrelevant stimuli is high, the difficulty of paired task would be low, and vice versa. The result supports our hypothesis; spatial cognition asymmetrically affected on temporal cognition when the difficulty of temporal task was significantly higher than that of spatial task.